Analisis Sudut Shading Device pada Fasade Tropis, Pendekatan Berbasis Lintasan Matahari Lokal, Studi Kasus Kota Kendari - Hasrul Nurliansyah; Dui Buana Mustakima; Cahyani Suhardi (JURNAL RUANG / ISSN : 2085-6962, 2026)
The high intensity of direct solar radiation on buildings in tropical regions makes shading device design one of the most effective passive strategies for achieving optimal thermal comfort and building energy efficiency. However, the reality of current design practice in determining shading device angles tends to be generic and has not been grounded in a thorough analysis of solar path trajectories or local climatic characteristics based on ideal angle calculations. This study employs a quantitative approach through solar path analysis and solar radiation simulation across varying shading device angles on eight facade orientations of buildings in Kendari City. The findings indicate that a 30° angle is the most effective for primary facades (north, south, west, and southwest), providing ideal shading performance during the critical period of 12:00–15:45 throughout the year. Nevertheless, facades receiving dominant solar exposure during morning hours - such as the southeast, east, and northeast orientations - require larger angles of 50°–55° to achieve effective shading performance. This study contributes a set of shading device angle recommendations grounded in local climatic data, which can serve as a design reference for tropical buildings in Kendari City.